Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Porous poly(ethylene glycol)-polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Torris, Arun A. T.; Lele, Ashish K.; Badiger, Manohar V. (Polymer International, 2015)
We report the synthesis of porous poly(ethylene glycol)-polyurethane (PEG-PU) hydrogels using PEG-4000 as a soft segment and 4,4-methylenebis(cyclohexylisocyanate) as a hard segment. The degree of swelling in the hydrogels could be controlled by varying the amount of crosslinking agent, namely 1,2,6-hexanetriol. Structural characterization of the hydrogels was performed using solid-state C-13 NMR and Fourier transform infrared spectroscopy. Wide-angle X-ray diffraction studies revealed the existence of crystalline domains of PEG and small-angle X-ray scattering studies showed the presence of lamellar microstructures. For generating a porous structure in the hydrogels, cryogenic treatment with lyophilization was used. Scanning electron microscopy and three-dimensional micro-computed tomography imaging of the hydrogels indicated the presence of interconnected pores. The mechanical strength of the hydrogels and xerogels was measured using dynamic mechanical analysis. The observed dynamic storage moduli (E) for the equilibrium swollen and dry gels were found to be 0.15 and 4.2 MPa, respectively. Interestingly, the porous PEG-PU xerogel also showed E of 5.6 MPa indicating a similar mechanical strength upon incorporating porosity into the gel matrix. Finally, preliminary cytocompatibility studies showed the ability of cells to proliferate in the hydrogels. These gels show promise for applications as scaffolds and implants in tissue engineering. (c) 2014 Society of Chemical Industry
Keywords: hydrogels; permeability; poly(ethylene glycol); polyurethane; porosity

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

High-Performance flexible solid-state supercapacitor with an extended nanoregime interface through in situ polymer electrolyte generation - Anothumakkool, Bihag; Torris, Arun A. T.; Veeliyath, Sajna; Vijayakumar, Vidyanand; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
{Here, we report an efficient strategy by which a significantly enhanced electrodeelectrolyte interface in an electrode for supercapacitor application could be accomplished by allowing in situ polymer gel electrolyte generation inside the nanopores of the electrodes. This unique and highly efficient strategy could be conceived by judiciously maintaining ultraviolet-triggered polymerization of a monomer mixture in the presence of a high-surface-area porous carbon. The method is very simple and scalable, and a prototype, flexible solid-state supercapacitor could even be demonstrated in an encapsulation-free condition by using the commercial-grade electrodes (thickness = 150 mu m
Keywords: cyclic voltametry; impedance analysis; in situ polymer generation; interface; polymer electrolyte; supercapacitor

Mechanically tunable curcumin incorporated polyurethane hydrogels as potential biomaterials - Divakaran, Anumon V.; Azad, Lal Busher; Surwase, Sachin S.; Torris, Arun A. T.; Badiger, Manohar V. (Chemistry of Materials, 2016)
We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4'-methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial cross linking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterization of hydrogels was performed using Fourier transform infrared spectroscopy, high-resolution mass spectrometry, UV and fluorescence spectroscopy. The wide-angle X-ray scattering studies revealed the existence of crystalline domains of PEG, and the small-angle X-ray scattering studies showed the presence of lamellar microstructures. Porous structure in the hydrogel was created by cryogenic treatment and lyophilization. Scanning electron microscopy and microcomputed tomography imaging of hydrogels showed the presence of interconnected pores. The mechanical strength of the hydrogels was measured using a universal testing machine. The observed tensile and breaking compression strengths for the equilibrium swollen gels were found to be in the range of 0.22-0.73 MPa and 1.65-4.6 MPa, respectively. Detailed in vitro biological experiments showed the biocompatibility of gels, cytostatic dosage of curcumin, selective toxicity toward cancer cell lines, and antibacterial property. These gels show promising applications as scaffolds and implants in tissue engineering.

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.

Tuning controlled release behavior of starch granules using nanofibrillated cellulose derived from waste sugarcane bagasse - Patil, Mayur D.; Patil, Vishal D.; Sapre, Aditya A.; Ambone, Tushar S.; Torris, Arun A. T.; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (ACS Sustainable Chemistry & Engineering, 2018)
Controlled release formulations help to encapsulate agrochemicals and deliver at a sustained rate. Growing environmental challenges have increased the need for controlled release systems based on sustainable feed-stocks. To this end, we report here the preparation and properties of a monolith-type controlled release granular formulation based on two ubiquitous biopolymers, starch and cellulose. Cellulose nanofibers (CNFs) derived from waste sugarcane bagasse were mixed with gelatinized maize starch and urea formaldehyde to yield nanocomposite granular formulation. Dimethyl phthalate (DMP) was used as model encapsulant. The morphology of CNFs and CNFreinforced starch granules was characterized by transmission electron microscopy, scanning electron microscopy, BET porosimetry, and X-ray tomography. Incorporation of only 2-4 wt % CNFs led to a significant reduction in porosity as compared to that for neat starch granules, while the water uptake was enhanced by 20-30%. Reinforcing starch with CNFs led to a significant reduction in initial release rate and yet higher overall release of DMP, thereby allowing effective utilization of entrapped chemicals. This interesting release behavior could be attributed to two competing factors, water uptake-induced diffusion and barrier effects rendered by nanocellulose network.

Water-in-acid gel polymer electrolyte realized through a phosphoric acid-enriched polyelectrolyte matrix toward solid-state supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Torris, Arun A. T.; Chandran, Nikhil M. K.; Nair, Sanoop B.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2018)
A new concept of water-in-acid gel polymer electrolytes (GPEs) is introduced. The simple and scalable UV-light-assisted synthesis of a copolymer matrix possessing polyelectrolyte behavior, followed by swelling in minimally diluted H3PO4 (15.1 M/88 wt % aqueous solution), effects formation of a high proton-conducting, self-standing, and mechanically stable polyelectrolyte GPE (PGPE). Retention of high mechanical stability despite the presence of a large amount of liquid species makes it a promising candidate for replacing conventional GPEs. The high proton conductivity (9.8 X 10(-2) S cm(-1)) of the PGPE at an ambient temperature of 303 K is attributed to the high concentration of the conducting species present in the polymer matrix. The PGPE-based polyaniline (PANI) supercapacitor device (PANI-1) with a mass loading of 1 mg cm(-2) exhibits a high specific gravimetric capacitance of 385 F g(-1) at a current density of 0.25 mA cm(-2). At the same current density, the PANI-5 device retains high gravimetric and areal capacitance values of 258 F g(-1) and 1288 mF cm(-2), respectively. The low equivalent series resistance value of 0.78 Omega (for the PANI-5 device) further proves the excellent electrode-electrolyte interface formed by the water-in-acid GPE. A 100% capacitance retention even after 9000 continuous charge-discharge cycles strongly indicates the feasibility of adopting water-in-acid GPEs in future supercapacitors.